Drawing Dynamical and Parameters Planes of Iterative Families and Methods. (21st November 2013) - Chicharro, Francisco I.; Cordero, Alicia; Torregrosa, Juan R.
Abstract : The complex dynamical analysis of the parametric fourth-order Kim's iterative family is made on quadratic polynomials, showing the MATLAB codes generated to draw the fractal images necessary to complete the study. The parameter spaces associated with the free critical points have been analyzed, showing the stable (and unstable) regions where the selection of the parameter will provide us the excellent schemes (or dreadful ones).